Gender, aging and longevity in humans: an update of an intriguing/neglected scenario paving the way to a gender-specific medicine - Ostan, Rita; Monti, Daniela; Gueresi, Paola; Bussolotto, Mauro; Franceschi, Claudio; Baggio, Giovannella (Clinical science (1979), 2016)
Data showing a remarkable gender difference in life expectancy and mortality, including survival to extreme age, are reviewed starting from clinical and demographic data and stressing the importance of a comprehensive historical perspective and a gene-environment/lifestyle interaction. Gender difference regarding prevalence and incidence of the most important age-related diseases, such as cardiovascular and neurodegenerative diseases, cancer, Type 2 diabetes, disability, autoimmunity and infections, are reviewed and updated with particular attention to the role of the immune system and immunosenescence. On the whole, gender differences appear to be pervasive and still poorly considered and investigated despite their biomedical relevance. The basic biological mechanisms responsible for gender differences in aging and longevity are quite complex and still poorly understood. The present review focuses on centenarians and their offspring as a model of healthy aging and summarizes available knowledge on three basic biological phenomena, i.e. age-related X chromosome inactivation skewing, gut microbiome changes and maternally inherited mitochondrial DNA genetic variants. In conclusion, an appropriate gender-specific medicine approach is urgently needed and should be systematically pursued in studies on healthy aging, longevity and age-related diseases, in a globalized world characterized by great gender differences which have a high impact on health and diseases.